MSME Transformation: Financing Solutions, Digitalization, and Sharia Business Ethics - Nurmalah; Syamsurizal (MUI Kota Pekanbaru, 2025)
This study aims to analyze the transformation of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through a sharia economics approach that covers three main pillars, namely sharia financing, Islam-based digitalization, and the application of sharia business ethics. Using the Systematic Literature Review (SLR) method, this study examines various relevant national and international publications from 2018 to 2025. The results show that Islamic financing models such as mudharabah, musyarakah, and murabahah play an important role in expanding access to capital for MSMEs and creating a more equitable and inclusive economic system. Meanwhile, digitalization and Islamic fintech innovation have proven to be able to increase efficiency, expand marketing networks, and accelerate transaction processes while maintaining the principles of sharia compliance. The application of Islamic business ethics also contributes to increased consumer confidence, business sustainability, and equitable economic welfare. However, challenges still arise in terms of sharia financial literacy, digital readiness, and consistency in the application of business ethics. This study emphasizes the importance of collaboration between the government, financial institutions, and academics to strengthen an inclusive, equitable, and sustainable sharia MSME ecosystem in the digital economy era.